ANTAGONISME FUNGI ENDOFIT DAUN JARAK PAGAR (JATROPHA CURCAS) TERHADAP FUSARIUM OXYSPORUM C2 PENYEBAB BUSUK UMBI PADA BAWANG MERAH IN VITRO - Nahdah, Fauziyyah; Sari, Noorkomala; Rizali, Akhmad; Wahdah, Rabiatul (Agrotechnology Research Journal, 2020)
Basal plate rot is a major disease on shallot caused by Fusarium oxysporum. Endophytic fungi is promising to use as antagonist agent to the pathogen. Endophyte is microbes that are living in plant cells and have an asymptomatic characteristic. Nowadays, fungal endophyte is believed to produce antimicrobial substances similar with their plant host's natural product. Jatropha curcas is one of the plants containing secondary metabolites that have antifungal activities. The research aimed to study the ability of endophyte from Jatropha curcas to inhibit the growth of Fusarium oxysporum. The dual culture method was used in this research and the data were analyzed by SPSS software. This antagonism test was conducted by 9 isolates endophyte and each plate consisted of 3 replicates. The result revealed endophyte fungal obtaining 9 isolates with the radial growth of 4,5 cm/2 days. Endophytes of Jatropha curcas L. were able to inhibit the growth of Fusarium oxysporum C2. The percentage of inhibition of Fusarium oxysporum causing of root blight diseases was controlled by up 38.27 - 74.48%. The highest percentage of inhibition is gained by B4b and the lowest of it is A2b. Our observations showed that each endophyte has a consistent linear trend. B4b still leaded as the highest strength to inhibit the growth of pathogen on the monitoring of 3, 5, and 7 days. Moreover, the ability of fungi endophyte from Jatropha curcas as antagonist agent to Fusarium oxysporum needs to be further examined by the in vivo method.